Aspek-Aspek Edukatif dalam Pembangunan Karakter Toleransi Berbasis Nilai-Nilai Al-Qur’an - Sukron Ma'mun; Nur Arfiyah Febriani (Ikatan Da'i Indonesia, 2026)
ABSTRACT This paper discusses the educational aspects in character building of tolerance based on qur’anic values. The al-maudhu'i interpretation method and a qualitative approach are used in this research to generate descriptive data through observations of the surahs and verses of the Qur'an, as well as science related to developing a tolerant character from a Qur'anic perspective. This study reveals that the educational aspects in character building of tolerance based on qur’anic values are found in three aspects namely first, the cognitive aspect, in this aspect there are 2 indicators, namely: understanding of pluralism, and understanding of harmony. Second, the affective aspect, in this aspect there are 3 indicators, namely: the attitude of avoiding prejudice, the attitude of non-discrimination and the attitude of respecting differences. Third, psychomotor/social aspects. In this aspect there are 3 indicators, namely: Giving freedom, building dialogue, and synergy in goodness.